Citra Perfeksionisme Wanita Pada Iklan Mustika Ratu Dalam Majalah Kartini - Wastiwi S., Sri (Seni Media Rekam ISI Surakarta, 2011)
The research of woman’s perfectionism image on advertisement of the Mustika Ratu beauty products, especially focused on advertisement of Lulur Krem dan Hand & Body Bengkoang Whitening products. The analysis technique used semiotic approach, in order to looking for sign, index, symbol, and connotation in the advertisement related to the products. Finally, the research found that the woman’s perfectionism image can be explained through several aspects, including model pose, costume, and narrative (text) existing in the advertisement. Key words: magazine, advertisement, woman, beauty product, perfectionism.